2019
DOI: 10.1038/s41598-019-42968-3
|View full text |Cite|
|
Sign up to set email alerts
|

Ocular biometry and refractive outcomes using two swept-source optical coherence tomography-based biometers with segmental or equivalent refractive indices

Abstract: This study compared the axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT), mean anterior corneal radius of curvature (Rm), and postoperative refractive outcomes obtained from two different swept-source optical coherence biometers, the ARGOS (Movu, Nagoya, Japan), which uses the segmental refractive index for each segment, and the IOLMaster 700 (Carl Zeiss Meditec, Jena, Germany), which uses an equivalent refractive index for the entire eye. One hundred and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 35 publications
3
56
3
1
Order By: Relevance
“…Calculating the IOL powers in highly myopic eyes also remains a challenge that often leads to unexpected postoperative hyperopia. 12,[26][27][28][29][30]56 In eyes with long ALs, both the Holladay 1 and Hoffer Q formulas exhibited a hyperopic trend. Several studies have reported the same result.…”
Section: Accuracy Of Iol Power Calculations Accordingmentioning
confidence: 96%
“…Calculating the IOL powers in highly myopic eyes also remains a challenge that often leads to unexpected postoperative hyperopia. 12,[26][27][28][29][30]56 In eyes with long ALs, both the Holladay 1 and Hoffer Q formulas exhibited a hyperopic trend. Several studies have reported the same result.…”
Section: Accuracy Of Iol Power Calculations Accordingmentioning
confidence: 96%
“…The other paper reported similar results with the Barrett Universal II and the SRK/T formulas, if the IOLMaster 700 (Zeiss Carl Meditec, Jena, Germany) was used; however, when using the Argos device (Movu, Aichi, Japan), the accuracy of biometry was again higher in the case of Barrett Universal II formula, which draws attention to the potential influencing role of the measuring device. 22…”
Section: Discussionmentioning
confidence: 99%
“…1 In particular, accurate axial length measurements are critical in calculating the correct intraocular lens (IOL) power and the tools for measuring axial length have undergone continuous evolution over the past nearly 20 years. [2][3][4][5][6][7][8] Naturally, as new technology has been introduced to perform biometric measurements, comparisons have been conducted to evaluate accuracy. [9][10][11][12][13][14] This includes the evolution from ultrasound biometry (UBM) to partial coherence interferometry (PCI), 9,15 while more recently, swept-source optical coherence tomography (SS-OCT) has been introduced.…”
Section: Introductionmentioning
confidence: 99%